Peak amplitude dependence of radiation properties of nonlinear Thomson scattering under an applied magnetic field - Gong, Xiaotian; Gu, Feiyang; Tian, Youwei (Frontiers in Physics, 2025)
The present study systematically investigates the peak amplitude dependence of nonlinear Thomson scattering radiation under an applied magnetic field through theoretical modelling and numerical simulations. A framework is established for the analysis of electron dynamics, spatial patterns and spectral distribution in combined fields of tightly focused circularly polarised Hermite-Gaussian lasers (a0 = 1–20) and magnetic fields (B0 = 0.5 kT). The findings of the study indicate a non-monotonic relationship, whereby optimal performance is observed at a0= 10, accompanied by exceptional collimation (angular divergence <2.5°) and peak intensity (approximately 107).This represents a 1,000-fold enhancement over low-amplitude regimes (a0 < 3). Spectral analysis reveals supercontinuum harmonics extending to ω/ω0 > 4,000, with maximum power concentrated at polar angles θm ≈ 2.5°. These findings advance magneto-optical control of relativistic scattering and provide guidelines for the optimisation of compact X-ray sources.